IMPROVING READING LITERACY WITH CANVA: A LITERATURE REVIEW ON INTERACTIVE LEARNING MEDIA - Kavel Kafabi Fahrozi; Khoirur Roisil Udzri; Inas Wildan Zamaroni; Dimas Adi Saputra; Dyan Yuliana (Journal on Research and Review of Educational Innovation, 2025)
Low student literacy can be caused by students' lack of interest in reading, facilities and infrastructure, an unsupportive environment, and the influence of technology. Literacy activities should be implemented in all schools and educational institutions to increase students' interest in good literacy skills. This research aims to analyze the application of Canva-based interactive learning media in improving students' reading literacy through the literature review method. The study collected and analyzed relevant literature from various sources, such as scientific journals, books, and research reports. The main focus is identifying Canva-based media's advantages in interactive learning and its influence on students' reading literacy. The study results show that Canva-based learning media positively impacts students' interest and reading ability by presenting interesting material, such as interactive visuals, animation, and multimedia elements. This media also supports independent and collaborative learning because it is easy to access and flexible to use. Based on the analysis of several pieces of literature, it can be concluded that Canva-based learning media has significant potential to support the effective development of students' reading literacy.